Single-cell RNA Sequencing Analysis Reveals New Immune Disorder Complexities in Hypersplenism - Zhao, Hai-chao; Chen, Chang-zhou; Song, Huang-qin; Wang, Xiao-xiao; Zhang, Lei; Zhao, Hao-liang; He, Jie-feng (Frontiers in Immunology, 2022)
Hypersplenism (HS) is a concomitant symptom of liver or blood disease. Not only does the treatment of HS face challenges, but its transcriptomes of individual cells is also unknown. Here, we generated the transcriptional profiles of 43,037 cells from four HS patients and one healthy person by the single-cell RNA sequencing and identified nine major cell types, including T-cells, B-cells, NK cells, hematopoietic stem cells, neutrophil cells, mast cells, endothelial cells, erythrocyte, and dendritic cells. Strikingly, the main feature was the lack of CCL5+ B-cells in HS and the presence of SESN1+ B cells in HCC-HS. In cell-cell interaction analysis, we found up-regulation of CD74-COPA and CD94-HLA-E in HS, which may be the main reason for the immune disorder of HS. We further explored HS-specifically enriched genes (such as FKBP5, ADAR, and RPS4Y1) and found that FKBP5 is highly expressed in HCC-HS, leading to immunosuppression. Through comprehensive analysis of single-cell transcriptome in HS, we provide deep insights into the genetic characteristics of HS, which explains why surgical removal of the spleen is beneficial for patient outcomes.